2015
DOI: 10.1126/sciadv.1500740
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of superparamagnetic dynamics in magnetic topological insulators

Abstract: The ferromagnetic state of topological insulators showing quantum anomalous Hall effect is surprisingly superparamagnetic.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
156
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 155 publications
(168 citation statements)
references
References 32 publications
9
156
1
2
Order By: Relevance
“…Other systems of interest are topologically protected surface states, edge states in quantum spin and anomalous quantum Hall systems, and surface states in Weyl semimetals. By choosing appropriate superconducting materials 22,23,33 it should be possible to extend the operating temperature range of the tSOT from tens of mK to tens of K (Fig. S1d) thus allowing investigation of a wide range of quantum systems.…”
mentioning
confidence: 99%
“…Other systems of interest are topologically protected surface states, edge states in quantum spin and anomalous quantum Hall systems, and surface states in Weyl semimetals. By choosing appropriate superconducting materials 22,23,33 it should be possible to extend the operating temperature range of the tSOT from tens of mK to tens of K (Fig. S1d) thus allowing investigation of a wide range of quantum systems.…”
mentioning
confidence: 99%
“…In contrast to conventional two-terminal/two-junction SQUIDs that display optimal sensitivity when flux biased to about a quarter of the flux quantum, the additional terminals and junctions allow optimal sensitivity at arbitrary applied flux, thus eliminating the magnetic field "blind spots". We demonstrate spin sensitivity of 5 to 8 µ B /Hz 1/2 over a continuous field range of 0 to 0.5 T, with promising applications for nanoscale scanning magnetic imaging.KEYWORDS: superconducting quantum interference device, SQUID on tip, nanoscale magnetic imaging, current-phase relations 2 In recent years, there has been a growing effort to develop and apply nanoscale magnetic imaging tools in order to address the rapidly evolving fields of nanomagnetism and spintronics.These include magnetic force microscopy (MFM) 1,2 , magnetic resonance force microscopy (MRFM) [3][4][5] , nitrogen vacancy (NV) centers sensors [6][7][8][9] , scanning Hall probe microscopy (SHPM) 10-12 , x-ray magnetic microscopy (XRM) 13 , and micro-or nano-superconducting quantum interference device (SQUID) [14][15][16][17][18][19][20] based scanning microscopy (SSM) [21][22][23][24][25][26][27][28][29][30][31][32] . Scanning micro-and nanoscale SQUIDs are of particular interest for magnetic imaging due to their high sensitivity and large bandwidth 15,19 .…”
mentioning
confidence: 99%
“…2,13,16 Indeed, a number of studies using global magnetization measurements 14,17,18 and magnetic force microscopy 19,20 have observed FM-like response in magnetically doped TI thin films. Surprisingly, however, recent scanning SQUID magnetic imaging 21 and transport studies, 22,23 as well as analysis of Kerr microscopy imaging, 24 have suggested the presence of a superparamagnetic (SPM) state in Cr-doped (Bi, Sb) 2 Te 3 films in which instead of a long-range FM order the magnetism is comprised of single-domain magnetic islands. These islands are of characteristic size of few tens of nanometers and are only weakly coupled to each other.…”
Section: Introductionmentioning
confidence: 99%
“…These islands are of characteristic size of few tens of nanometers and are only weakly coupled to each other. 21 The possible presence of a SPM order has important implications for the properties of the QAH state. The first key consideration is that if the QAH state can indeed be induced by a SPM order, such coexistence can be present only at temperatures well below the SPM blocking temperature, T≪T B , since at higher temperatures the QAH state will be destroyed by thermally activated magnetization reversals of the SPM islands.…”
Section: Introductionmentioning
confidence: 99%